Machine learning to identify risk factors associated with the development of ventilated hospital-acquired pneumonia and mortality: implications for antibiotic therapy selection - Sophonsri, Anthony; Lou, Mimi; Ny, Pamela; Minejima, Emi; Nieberg, Paul; Wong-Beringer, Annie (Frontiers in Medicine, 2023)
Background: Among patients with nosocomial bacterial pneumonia, those who decompensated to requiring mechanical ventilation (vHABP) faced highest mortality. The objectives of this study were to identify risk factors associated with the development and mortality of vHABP and to evaluate antibiotic management. Methods: A multicenter retrospective cohort study of adult patients admitted with HABP during 2014-2019 was performed. Groups were stratified by vHABP, nvHABP, and VABP and compared on demographics, clinical characteristics, treatment and outcomes. Multivariable models were generated via machine learning to identify risk factors for progression to vHABP and pneumonia-associated mortality for each cohort. Results: 457 patients (32% in nvHABP, 37% vHABP, and 31% VABP) were evaluated. vHABP and nvHABP groups were similar in age (median age 66.4) with 77% having multiple comorbidities; more vHABP group had liver disease (18.2% vs 7.7% p=0.005), alcohol use disorder (27% vs 7.1%, p<0.0001), and were hospitalized within the past 30 days (30.4% vs 19.5%, p=0.02). An immediate need for ventilatory support occurred in 70% of vHABP patients on the day of diagnosis. Mortality was the highest in vHABP followed by VABP and nvHABP groups (44.6% vs 36% vs 14.3%, p<0.0001). Nearly all (96%) vHABP group had positive cultures, with Gram-negative pathogens accounting for 58.8% whereby 33.0% were resistant to extended-spectrum beta-lactams (ESBLs), ceftriaxone (17.5%), fluoroquinolones (20.6%), and carbapenem (12.4%). Up to half of the vHABP patients with ESBL-Enterobacterales or P. aeruginosa did not receive an effective empiric regimen; over 50% increase in mortality rate was observed in whom effective therapy was initiated past the day of pneumonia diagnosis. Risk factors associated with vHABP development were alcohol use disorder, APACHE II score, vasopressor therapy prior to infection, and culture positive for ESBL-Enterobacterales whereas history of hospitalization in the past 30 days, active malignancy, isolation of ceftriaxone-resistant pathogens or Pseudomonas aeruginosa, and vasopressor therapy were risk factors for vHABP-associated mortality. Conclusions: The risk factors identified in this study provide actionable data for clinicians to help identify those at risk for vHABP at the onset of pneumonia and to target antimicrobial stewardship efforts to improve treatment success.